2002
DOI: 10.1089/10799900252952253
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitutions in Loop BC and Helix C Affect Antigenic Properties of Helix D in Hybrid IFN-α21a/α2c Molecules

Abstract: We compared the antigenic properties of human interferon-alpha2c (IFN-alpha2c), IFN-alpha21a, hybrids IFN-alpha21a/alpha2c, and their mutants, using a panel of 27 anti-IFN-alpha1, anti-IFN-alpha2, and anti-IFN-alpha8/1/8 monoclonal antibodies (mAb). After immunoanalysis by ELISA, we found parental IFN-alpha2c and IFN-alpha21a to be antigenically distinct. Lack of reactivity of anti-IFN-alpha1 mAb with IFN-alpha21a indicated an antigenic distinction between subtypes alpha1 and alpha21a. The antigenic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Finally, we chose to dock the loop in the SD1 subdomain of IFNAR1 enclosing the 64G12 epitope with IFN residues located at the C-terminal of helix D (Figure 6). This is in agreement with Schmeisser et al, (41) who showed that amino acid substitutions in loop BC, helix C, and helix D alter the interaction between IFN-R and its receptor and influence the threshold of activation of the biological response.…”
Section: Ifnar1 Residues Involved In Interferon Bindingsupporting
confidence: 92%
“…Finally, we chose to dock the loop in the SD1 subdomain of IFNAR1 enclosing the 64G12 epitope with IFN residues located at the C-terminal of helix D (Figure 6). This is in agreement with Schmeisser et al, (41) who showed that amino acid substitutions in loop BC, helix C, and helix D alter the interaction between IFN-R and its receptor and influence the threshold of activation of the biological response.…”
Section: Ifnar1 Residues Involved In Interferon Bindingsupporting
confidence: 92%